Students’ Skill in Writing Recount Text at the Eleventh Grade Students at Senior High Schoo1 8 Jambi City - Rani Meilanny Saragih; Khidayatul Munawwaroh; Ridho Praja Dinata (JELT: Journal of English Language Teaching, 2022)
The purpose of this research was to determine the students' skill in writing recount text at Senior High School 8 Jambi City. This research was conducted at Senior High School 8 Jambi City. The research design used quantitative. The approved in this research is descriptive quantitative. The population of this research was students of class XI at Senior High School 8 Jambi City. The sample of this research was 36 students of class XI IPA 1 selected using simple random sampling. This research used a written test instrument, a written test in the form of an essay test to make a recount text about best experience in holiday. The technique of data collection of this research used test as a research instrument. The technique of data analysis of this research are tabulating the students’ score, calculating the students’ score, and give the score classification. This finding shows that students’ skill in writing recount text are based on generic structure in writing recount text. First, the orientation with an average of 8,94 or including excellent criteria, second, the events with an average of 9,17 or including excellent criteria, and lastly, the reorientation with an average of 7,28 or including good criteria. From the results of the data, 2 generic structure are classified as excellent and 1 generic structure that classified as good. This proves that at the level of students’ skill in writing recount text academically, they are still classified as excellent.